Highly stable, luminescent core–shell type methylammonium–octylammonium lead bromide layered perovskite nanoparticles. Issue 44 (11th May 2016) - Bhaumik, Saikat; Veldhuis, Sjoerd A.; Ng, Yan Fong; Li, Mingjie; Muduli, Subas Kumar; Sum, Tze Chien; Damodaran, Bahulayan; Mhaisalkar, Subodh; Mathews, Nripan
Abstract : Perovskite–perovskite core–shell type nanoparticles with a high photoluminescence quantum yield and long term ambient stability. Abstract : A new protocol for the synthesis of a highly stable (over 2 months under ambient conditions) solution-processed core–shell type structure of mixed methylammonium–octylammonium lead bromide perovskite nanoparticles (5–12 nm), having spherical shape, color tunability in the blue to green spectral region (438–521 nm) and a high photoluminescence quantum yield (PLQY) of up to 92% is described. The color tunability, high PLQY and stability are due to the quantum confinement imparted by the crystal engineering associated with core–shell nanoparticle formation during growth.